2020
DOI: 10.1088/2051-672x/ab7ae5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tribological behavior of nickel-nano Si3N4 composite coatings fabricated by pulsed electroplating process

Abstract: Pure nickel and nano-composite nickel-silicon nitride (Si 3 N 4) coatings were fabricated using pulsed current electrodeposition technique. A control sample for each coating was created and the effect of current density, duty cycle, and pulse frequency on the tribological properties of the electrodeposited coatings was investigated by altering these parameters. X-ray diffraction, scanning electron microscopy and pin-on-disk tests were performed to assess the properties of the fabricated coatings. X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…104 Furthermore, metal-Si 3 N 4 composite coatings are also commonly used as wear-resistant films. [105][106][107]…”
Section: Sn-cmcs With Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…104 Furthermore, metal-Si 3 N 4 composite coatings are also commonly used as wear-resistant films. [105][106][107]…”
Section: Sn-cmcs With Coatingmentioning
confidence: 99%
“…It was concluded that gas lubrication was similar to water lubrication which was often used to adjust friction performance 104 . Furthermore, metal–Si 3 N 4 composite coatings are also commonly used as wear‐resistant films 105–107 …”
Section: Friction and Wear Performances Of Sn‐cmcs With Layered Struc...mentioning
confidence: 99%
“…The higher the bond strength between resin and fiber was, the better the mechanical properties of composite. In addition, it is beneficial to the conduction of friction heat and the transfer of internal stress, effectively reducing the wear rate of the contact zone [25]. The ILSS cross-section of phenolic resin contact strip in Figure 7(c) was serrated on the interface between CF and phenolic resin, indicating a high toughness of the interface.…”
Section: Wear Mechanism Of Cfrcs and Pccs Against Coppermentioning
confidence: 99%
“…18,19 Pulse current (PC) and pulse reverse current (PRC) electrodeposition techniques have recently attracted many researchers for the synthesis of composite coatings in comparison to the conventional DC electrodeposition techniques. 20 In PC and PRC electrodeposition techniques, the adjustment of the applied potential, duty cycle, cathodic/anodic pulses, and pulse waveform can alter the surface morphology, elemental composition, and microstructure of the resulting composite coatings. 21 The charging and discharging of the electric double layer around the cathode occur due to the periodic alteration of the current between zero to positive values in the PC mode, and from positive to negative values in the PRC mode.…”
Section: Introductionmentioning
confidence: 99%